Risk of endothelial dysfunction in streptozotocin-induced diabetic Sprague-Dawley rats: Nitric oxide in focus - M.L. Jidda J.M. Bunza M.K. Dallatu L.S. Bilbis A.J. Alhassan Muhammad Yelwa Gwarzo A.A. Ngaski A.F. Chiroma S.L. Kakako Maryam Kasimu B.M. Yale M. Kasimu S. Haruna K.A. Ogunwale A. K. Bello Ibrahim Kalle Kwaifa (Sokoto Journal of Medical Laboratory Science)
Endothelial dysfunction in diabetes manifests in part as  reduction of nitric oxide (NO) bioavailability, which leads to inadequate relaxation of the vascular smooth muscle and a disparity between the vasoconstrictive and vasorelaxant intracellular pathways which favours a rise in vasoconstriction. In this current work, we evaluated serum Nitric oxide (NO) concentration and the activity of Nitric oxide synthase (NOS) in streptozotocin-induced diabetic male and female rats' serum. Our results showed initial and final fasting blood glucose concentration 5.30±0.16mmol/l and 5.24±.015mmol/l versus 5.68±0.18mmol/l and 5.43±0.15mmol/l in male and female controls. Among the diabetic rats, the initial and final fasting blood glucose concentration was 17.50±1.91mmol/l and 15.68±2.84mmol/l versus 20.50±4.76mmol/l and 19.40±4.13mmol/l in male and female rats respectively. NO concentration was 106.12±7.23μmol/l and 131.81±12.54 μmol/l in male and female control rats compared to 52.38±3.01μmol/l and 65.29±16.19 μmol/l in male and female diabetic rats respectively. Serum activity of NOS were 133.72±10.92μIU/l and 156.06±18.22 μIU/l in control male and female rats compared to 98.01±1.48 μIU/l, 78.89±8.39μIU/l in diabetic male and female rats respectively. The difference in both NO concentration and NOS activity was significant between diabetics and non-diabetic rats as well as between male and female diabetics rats (p< 0.05). The endothelial dysfunction in diabetic animals regardless of gender may be an initial pointer to upcoming pathogenesis and we recommend routine evaluation of NO concentration and NOS activities among diabetics.